Design of Data warehouse to Analyze CMMS Data - علي سليمان (Latakia University Journal -Engineering Sciences Series, 2022)
In this paper, a system based on data warehouse technology and remote database modeling is designed to receive data related to the maintenance and analysis of the machines in order to reach results that contribute to the decision making that may relate to the state of machines or types of faults or the time of occurrence. Lattakia International. The system relies on a Compaq server, an Oracle 11 database engine, and Oracle Developer to create reports and searches. The results showed that the use of data warehouse technologies in the analysis of computer maintenance systems data reduces the time required for the completion of queries on the data and allows generation of many reports that need to be generated using the traditional database to write a large number of queries manually.